(3QbGHI OSJhQjI GdbhGfjf (B:s ((3GdeHGOF GdfXQjI hGdJWHjbGJ GdLhgQjI(B) /s - (3YHO GdhgGH, eMeO QaYJ,s 1942- ((3GdEScfOQjI, eUQ (B:s (3OGQ GdLGeYI GdLOjOI ddWHGYI hGdfTQ hGdJhRjY,s, 2011)
(3Ef eTcdI QbGHI OSJhQjI GdbhGfjf ef GdeTGcd GdgGeI GdJj JKhQ aj GdHdGO GdOjebQGWjI, GdJj JcQS eHOC GdOhdI GdbGfhfjI GdJj JNVY ajgG GdSdWGJ GdYGeI GdMGceI eKd GdCaQGO GdeMchejf deHOC GdeTQhYjI Ch SjGOI GdbGfhf, hdG Tc aj Cf GdOSJhQ HGYJHGQg beI GdbhGYO GdbGfhfjI aj Cj OhdI jLH Cf jchf dg GdSeh hGdYdh, HMjK jCJj Ydi beI GdfXGe GdbGfhfj aj GdOhdI(B. (3hef Ke JOYh GdMGLI hGdVQhQI dhLhO JfXje bGfhfj Ch OSJhQj jcad hjVef JMbjb Ydh hSeh bhGYO GdOSJhQ aj GdOhdI GdOjebQGWjI(B. (3gPG GdJfXje bO jfU Ydjg GdOSJhQ UQGMI, ajfTF eMceI OSJhQjI YdjG jaQW HgG QbGHI OSJhQjI GdbhGfjf GdHQdeGfjI, eKdeG gh GdhVY aj GdOSJhQ GdeUQj GdUGOQ YGe (B1971 (3hGdeWHb MJi GdBf, hEf cGfJ QbGHI GdeMceI GdOSJhQjI GdYdjG JTed HLGfH HMK OSJhQjI GdbhGfjf OSJhQjI GddhGFM GdUGOQI ef GdSdWI GdJfajPjI cPdc WHbG deG fU Ydjg OSJhQ (B1971. (3hbO jfTF GdOSJhQ eMceI YdjG Ohf Cf jSejgG OSJhQjI, hJchf gPg GdeMceI Ydi beI GdJfXje GdbVGFj GdYGe aj GdOhdI, hef Ke agj HMce hUagG GfJRYJ dfaSgG Mb QbGHI OSJhQjI GdbhGfjf HQZe YOe GdfU GdUQjM aj GdOSJhQ Ydi gPG GdGNJUGU(B. (3haj dHfGf, bO Je JYOjd GdeGOI (B19 (3ef OSJhQ GdLeghQjI GddHfGfjI YGe (B1990. (3hCUHMJ JbU Ydi Cf jfTC eLdS OSJhQj deQGbHI OSJhQjI GdbhGfjf hGdHJ aj GdfRGYGJ hGdWYhf GdfGTFI Yf GdGfJNGHGJ GdQFGSjI hGdfjGHjI(B. (3hbO UOQ GdbGfhf Qbe (B250 (3dYGe (B1993 (3HEfTGA GdeLdS GdOSJhQj, GdPj JVef bhGYO JTcjdg hGNJUGUGJg hGdCUhd GdELQGFjI GdeJHYI CeGeg(B. (3hSha jYQV GdOcJhQ fYeJ YHO GdhgGH hjbOQ ef GdJaUjd aj gPg GdOQGSI dJTcjd hGNJUGUGJ GdeLdS GdOSJhQj GddHfGfj, hcPdc ddWHjYI GdbGfhfjI ddeLdS ef MjK chfg gjFI SjGSjI Ch gjFI bVGFjI, HGdEVGaI Edi WHjYI GdQbGHI GdJj jeGQSgG aj eLGd QbGHI OSJhQjI GdbhGfjf, hgd gj JbUQ Ydi GdfhGMj GdbGfhfjI Ce jecf Cf JeJO Edi bOQ ef GdedGAeI GdSjGSjI, hCNjQG YQV dJWHjbGJ QbGHI GdOSJhQjI GdJj jeGQSgG GdeLdS GdOSJhQj aj dHfGf(B.s
Keywords: (3GdeQGLYI GdbVGFjIs -- (3eUQs; (3GdQbGHI GdbVGFjI Ydi OSJhQjI GdbhGfjfs -- (3eUQs; (3GdbGfhf GdOSJhQjs -- (3eUQs